Pathogenicity of chicken and pigeon isolates of Newcastle disease virus - MISHRA, S; KATARIA, J M.; SAH, R L; VERMA, K C; MISHRA, J P (The Indian Journal of Animal Sciences, 2013)
Pathogenicity of chicken and pigeon isolates of Newcastle disease virus was studied in 3-week-old chickens. Clinical signs following inoculation of chicken isolate by oronasal route were observed after an incubation period of 4-5 days that included dullness, depression, dyspnoea, diarrhoea and leg paralysis with mortality of 60%. Pigeon isolate infected group exhibited very mild clinical signs with mortality of 6%. Postmortem examination of birds infected with chicken isolate revealed haemorrhages at the tip of the glands of proventriculus and caecal tonsil, while in pigeon isolate group, no gross changes were observed. However, histopathological changes were seen invariably in bursa of fabricius, spleen, caecal tonsil and trachea of both the groups. Virus was also isolated from various organs of both the groups from 5-10 days post infection.